Analysis of Close Encounters With Ganymede and Callisto Using a Genetic n-Body Algorithm - Winter, Philip M.; Galiazzo, Mattia A.; Maindl, Thomas I. (Frontiers in Astronomy and Space Sciences, 2018)
In this work we describe a genetic algorithm which is used in order to study orbits of minor bodies in the frames of close encounters. We find that the algorithm in combination with standard orbital numerical integrators can be used as a good proxy for finding typical orbits of minor bodies in close encounters with planets and even their moons, saving a lot of computational time compared t0 long-term orbital numerical integrations. Here, we study close encounters of Centaurs with Callisto and Ganymede in particular. We also perform n-body numerical simulations for comparison. We find typical impact velocities to be between v rel = 20[v esc ] and v rel = 30[v esc ] for Ganymede and between v rel = 25[v esc ] and v rel = 35[v esc ] for Callisto.